Factors Affecting Short Term Outcome in Isolated Congenital Diaphragmatic Hernia: A Cohort Study from A Tertiary Surgical Center - Nasiri, Seyyed Javad; Adel, Maryam Ghavami; Keramati, Mohammad Reza (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2017)
Background: The mortality rate of Congenital Diaphragmatic Hernia (CDH) is still high in many centers. Most important factors influencing the outcome are pulmonary hypoplasia and associated anomalies. In this study, postnatal factors affecting short term outcome of patients with isolated CDH will be studied in an educational children hospital. Methods : This is a historical cohort study, on newborns with isolated posterolateral congenital diaphragmatic hernia from 2005 to 2015. Relative risks of variables for the short term outcome (Discharged alive or expired) were calculated. We also analyzed the highest PaO2, which was measured during the course of the management in the patients. Location of the liver and stomach were detected, too. Results: Fifty-three patients were studied, including 28(52.8%) male and 25(47.2%) female. Mean Gestational Age (GA) was 38 weeks (Range: 33-40) and mean body weight was 3001.22 (Range: 1300 4200) grams. Forty-two (79.2%) presented with left sided hernia, and 10(18.9%) had right sided defect. Thirty-two (60.4 %) patients discharged alive, and 21(39.6%) expired. Mortality rate for right sided hernias was 70% (7/10), and for left sided ones was 31% (13/42). Sex, weight, GA, stomach and liver herniation had no significant effect on survival. Side of involvement, time of presentation (Onset of symptoms), first measured PaO2, and first measured PaCO2, had significant influences on survival. Conclusion: According to our analysis, side of hernia, time of onset of symptoms, and initial PaO2 and PaCO2 are factors predicting survival in children with congenital diaphragmatic hernia. Although, we may predict the early outcome of the patients, more studies are needed in this regard. Chatt Maa Shi Hosp Med Coll J; Vol.15 (2); Jul 2016; Page 30-32